The Effect of Motivation and Organizational Commitment on Job Satisfaction and Its Impact on Teacher Performance In Private Junior High Schools in Lempuing District - Hendrik, Hendrik; Rahayu, Sri; Asiati, Diah Isnaini (International Journal of Marketing & Human Resource Research, 2025)
This study aims to determine the effect of motivation and organizational commitment on job satisfaction and its impact on teacher performance at a private junior high school in the sub-district of Lempuing, Ogan Komering Ilir. This type of research is associative. The variables used in this study are Motivation, Organizational Commitment, Satisfaction, and Performance. The sample in this study was teachers, totaling 110 people. The study employed primary data, collecting data using questionnaire techniques. The analysis technique uses SEM. The results of the survey prove that 1) motivation has no significant effect on teacher job satisfaction. 2) Motivation has a significant positive effect on teacher performance. 3) Commitment has no significant effect on teacher satisfaction in Lempuing Subdistrict. 4) Work commitment does not have a significant effect on teacher job satisfaction in the sub-district of Lempuing. 5) Satisfaction has no significant effect on the performance of teachers in private junior high schools in the sub-district of Lempuing, Ogan Komering Ilir.